THE ROLE OF CONTEXT AND ITS IMPACT ON THE COHERENCE OF POETIC TEXTS: EXCERPTS FROM THE COLLECTION "MINARETS OF LONGING" BY THE ALGERIAN POET SAAD MARDAF - Mahfoud MALAOUI (Ziglôbitha)
Abstract: Modern linguistic studies focus on the importance of context in determining meaning, as language forms the foundation for tracking the textual structure systematically by linking words, sentences, and social context. This research aims to analyze the collection "Minarets of Longing" to clarify the role of context in explaining ambiguities, weighing possibilities, and affirming clear meanings through usage. The results show that context, in its various forms, plays a prominent role in linguistic studies, and that poetic texts are no less important than prose in this regard. The beauty of poetic texts is also revealed through the linguistic elements associated with the poet's speech, as well as the direct relationship between the sender and the receiver through a conscious reading of the text in light of the social school (Firthian), which focuses on social context in modern linguistic studies.